Factors associated with health care utilization and catastrophic health expenditure among cancer patients in China: Evidence from the China health and retirement longitudinal study - Deng, Penghong; Fu, Yu; Chen, Mingsheng; Si, Lei (Frontiers in Public Health, 2022)
Background: Cancer, the leading cause of mortality in China, is a significant burden on patients, their families, the medical system, and society at large. However, there is minimal data on health service utilization and catastrophic health expenditure (CHE) among cancer patients in China. The objective of this study was to identify factors associated with health care utilization and CHE in Chinese cancer patients. Methods: The 2018 wave of a nationally representative dataset, the China Health and Retirement Longitudinal Study, was used in our study. Of 18968 respondents recruited for the analysis, 388 were clinically diagnosed with cancer. CHE was defined as household health expenditure that exceeded 40% of non-food household expenses. A binary logistic regression model was used to identify the risks of cancer exposure among all participants, along with the likelihood of CHE in households with cancer patients at the 40% threshold. A negative binomial regression model was used to identify determinants of health service utilization among cancer patients. Results: Contracting a family physician (incidence rate ratio IRR:2.38, 1.18-4.77), Urban Employee Basic Medical Insurance (IRR:4.02, 1.91-8.46, compared to the uninsured), Urban and Rural Resident Basic Medical Insurance (IRR:3.08, 1.46-6.49, compared to the uninsured), and higher per-capita household consumption were positively associated with inpatient service utilization. Patients with a college education and above reported a greater number of outpatient visits (IRR:5.78, 2.56-13.02) but fewer inpatient hospital days (IRR:0.37, 0.20-0.67). Being diagnosed with a non-cancer chronic non-communicable disease was associated with an increased number of outpatient visits (IRR:1.20, 1.10-1.31). Of the 388 participants, 50.1% of households had CHE, which was negatively correlated with a larger household size (odds ratio OR:0.52, 0.32-0.86) and lower socioeconomic status (for quintile 5 [lowest group] OR:0.32, 0.14-0.72). Conclusions: The socioeconomic characteristics of cancer patients had a considerable impact on their healthcare utilization. Individualized and targeted strategies for cancer management should be implemented to identify high-risk populations and trace the utilization of care among Chinese cancer patients. Strategic purchasing models in cancer care and social health insurance with expanded benefits packages for cancer patients are crucial to tackling the cancer burden in China.